Resistance gene cloning from a wild crop relative by sequence capture and association genetics - Arora, Sanu; Steuernagel, Burkhard; Gaurav, Kumar; Chandramohan, Sutha; Long, Yunming; Matny, Oadi; Johnson, Ryan; Enk, Jacob; Periyannan, Sambasivam; Singh, Narinder; Md Hatta, M. Asyraf; Athiyannan, Naveenkumar; et al. (Nature Research, 2019)
Disease resistance (R) genes from wild relatives could be used to engineer broad-spectrum resistance in domesticated crops. We combined association genetics with R gene enrichment sequencing (AgRenSeq) to exploit pan-genome variation in wild diploid wheat and rapidly clone four stem rust resistance genes. AgRenSeq enables R gene cloning in any crop that has a diverse germplasm panel.